Case report: Diagnosis and intervention of a non-24-h sleep–wake disorder in a sighted child with a psychiatric disorder - Estivill-Domènech, Carla; Rodriguez-Morilla, Beatriz; Estivill, Eduard; Madrid, Juan Antonio (Frontiers in Psychiatry, 2024)
Circadian rhythm sleep–wake disorders (CRSWD) are sleep dysfunctions related to circadian functioning. They are characterized by symptoms of insomnia or excessive sleepiness that occur because the intrinsic circadian pacemaker is not entrained to a 24-h light/dark cycle. Affected individuals with a free-running disorder or hypernycthemeral syndrome (N24SWD) have a longer sleep–wake cycle that produces a sleep pattern that typically delays each day. The disorder is seen in 70% of blind people, and among people with healthy vision, it is a rare pathology. Among sighted cases, 80% are young men and 28% have a psychiatric disorder. The patient was a 14-year-old boy with a psychiatric pathology diagnosed with a PANDAS syndrome (pediatric autoimmune neuropsychiatric disorders associated with streptococci), a sudden acute and debilitating onset of intense anxiety and mood lability accompanied by obsessive compulsive-like issues and/or tics, in association with a streptococcal A infection that occurs immediately prior to the symptoms. As a comorbidity, he exhibited severe insomnia due to an irregular sleep pattern that strongly delayed his sleep schedule day to day. It affected his daily routines, as he was not going to school, and aggravated, furthermore, the psychiatric symptoms. He was referred for sleep consultation, where the case was explored by ambulatory circadian monitoring (ACM) using the novel system Kronowise® (Chronolab, University of Murcia) and diagnosed with a non-24-h sleep–wake disorder (N24SWD). The first treatment approach for the patient was focused on improving symptoms during the acute infection and psychiatric symptoms. Additionally, sleep pathology was treated by light therapy and melatonin. After 8 months and different trials, it was possible to establish a treatment to normalize the symptoms and fix his sleep rhythm in a normal schedule as well as to reduce anxious symptoms during the day. The association of PANDAS and N24SWD has not previously been reported in the literature.